خطاب المقدس في أدب ابراهيم الكوني - لهلالي, ابتسام (جامعة الوادي - university of Eloued, 2020)
اشتغلت نصوص ابراهيم الكوني على توظيف الجانب الثقافي، وترجمة حياة البدوي الطارقي وثقافته الاجتماعية والفكرية. انعكس تأثر الروائي الليبي ابراهيم الكوني بعالم الصحراء، على نصوصه الروائية، فجاءت أعماله تعبيرا عن هواجسه المتزاحمة مع الهم والوجع والغربة والحنين، ومشاعره التي تأسرها الصحراء وقوانينها المقدسة التي لافكاك منها ibrahim El-kouni texts worked on employing the cultural aspect, And the translating the life of Bedouin al-tariqi and his social and intellectual culture. the influence of the Libyan novelist Ibrahim Al-kony on the the desert was reflected in his novel texts. On his fictional texts, his works came as an expression of his obsessive competitions with anxiety, soreness , alienation and nostalgia, And his feelings captured by the desert and its sacred laws that do not escape them.
مقال
Keywords: الاسطو رة ; الخرافة ; الط ; ارق ; المقدس; the sacret, the Myth., the fable, The fantastique, the populaire history..